2021
DOI: 10.3390/ijms22094527
|View full text |Cite
|
Sign up to set email alerts
|

Ovariectomy-Induced Hepatic Lipid and Cytochrome P450 Dysmetabolism Precedes Serum Dyslipidemia

Abstract: Ovarian hormone deficiency leads to increased body weight, visceral adiposity, fatty liver and disorders associated with menopausal metabolic syndrome. To better understand the underlying mechanisms of these disorders in their early phases of development, we investigated the effect of ovariectomy on lipid and glucose metabolism. Compared to sham-operated controls, ovariectomized Wistar female rats markedly increased whole body and visceral adipose tissue weight (p ˂ 0.05) and exhibited insulin resistance in pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…In addition, some inflammatory pathways, in particular those related to NFκB, are activated by methylglyoxal ( Neves, et al, 2019 ). According to our previous results ( Malinska, et al, 2021 ), hepatic methylglyoxal concentrations well correlated with hepatic triglycerides concentrations. Thus, mitigation of dicarbonyl stress through decreased methylglyoxal and increased Glo1 expression, can protect against NAFLD development and/or progression.…”
Section: Discussionsupporting
confidence: 76%
“…In addition, some inflammatory pathways, in particular those related to NFκB, are activated by methylglyoxal ( Neves, et al, 2019 ). According to our previous results ( Malinska, et al, 2021 ), hepatic methylglyoxal concentrations well correlated with hepatic triglycerides concentrations. Thus, mitigation of dicarbonyl stress through decreased methylglyoxal and increased Glo1 expression, can protect against NAFLD development and/or progression.…”
Section: Discussionsupporting
confidence: 76%
“…The pathological accumulation of extracellular matrix proteins has metabolic consequences including insulin resistance and adipose tissue inflammation [61,62]. Furthermore, a study conducted by Malinská et al found that the interscapular BAT in the Ovx rats exhibited decreased fatty acid oxidation, lipogenesis, and lipolysis, which might lead to visceral adiposity as well as triglyceride accumulation [63]. Our results are supported by previous literature in which BAT metabolic pathways were impaired in response to ovariectomy and might have contributed to postmenopausal obesity in the long run [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, these rather robust changes in the mass and content of organs and tissues were not accompanied by changes in circulating FFA, and cholesterol, non-fasting glycemia, circulating insulin and glucagon. The explanation could be from previous experimental study in Wistar rats [ 38 ] indicating that organ changes after ovariectomy could precede changes in circulating factors, in this case not only changes of circulating lipids but also of parameters associated with glucose homeostasis. Regarding changes in circulating serum lipids, triglycerides decreased after ovariectomy and increased when estradiol was substituted after ovariectomy.…”
Section: Discussionmentioning
confidence: 99%